Development of multi-input multi-output converter for decarbonization energy system - Baharom, Rahimi; Ghazali, Mohd Shukri Mohd (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Decarbonization energy systems include a range of renewable energy sources, such as solar, wind, hydro, and geothermal. These sources generate electricity with minimal carbon emissions and can be used in various applications, including power generation, heating, and transportation. Therefore, the use of a multi-input multi-output (MIMO) converter is becoming increasingly important in decarbonization energy systems. This is because the integration of multiple renewable energy sources, requires a power converter that can manage multiple inputs and outputs efficiently. This paper presents the development of a MIMO converter using a single-phase matrix converter for decarbonization energy systems. The proposed converter is capable of integrating multiple renewable energy sources and can be used in a microgrid application, thus removing the need of multiple converters. The design and analysis of the converter are presented, including the selection of power switches and control strategy. The performance of the converter is evaluated through experimental results, demonstrating its effectiveness in managing multiple inputs and outputs using a single power converter circuit. The results indicate that the proposed converter is a promising solution for decarbonization energy systems, contributing to the development of sustainable energy systems.